Modern Postural Yoga and the Health-Spirituality-Neoliberalism Nexus - Di Placido, Matteo; Strhan, Anna; Palmisano, Stefania (Fieldwork in Religion, 2022)
The practice of yoga has become an integral part of practitioners’ lifestyles, spirituality and therapeutic paths across the world, not to mention institutional and governmental interventions of a pedagogical, rehabilitative and political nature in settings as diverse as schools, hospitals and prisons. While social science literature has explored some of these areas of analysis, we currently know little about how particular conceptions of health and wellbeing, of the sacred and of the economic-political continuum overlap, diverge and reciprocally influence each other, with reference to yoga and beyond. Using the example of “modern postural yoga”, this article aims to provide a preliminary account of what we term the Health-Spirituality-Neoliberalism Nexus, that is, of the ways in which different “social fields”, such as the medical/therapeutic, the spiritual/religious and the political/economic fields, are partly governed by the same practical-discursive logics and display profound “symbiotic relationships”. More specifically, this article elucidates how specific health discourses, centred around practitioners’ self-care, self-responsibility and self-control, dominate not only the medical/therapeutic field, but also the landscape of contemporary spiritualities and the widespread neoliberal ethos that characterizes the current social, political and economic model of Westernized societies. Here, the categories of physical and psychological health, the idea of a fulfilling spiritual life, and economic success display deep “elective affinities” that we seek to uncover by mobilizing a series of foundational sociological concepts such as the Bourdieusian notion of “field” and a Foucauldian reading of “biopolitics” and “governmentality”.